2016
DOI: 10.1140/epjc/s10052-016-3975-2
|View full text |Cite
|
Sign up to set email alerts
|

Multi-TeV flaring from blazars: Markarian 421 as a case study

Abstract: The TeV blazar Markarian 421 underwent multiTeV flaring during April 2004 and simultaneously observations in the X-ray and TeV energies were made. It was observed that the TeV outbursts had no counterparts in the lower energy range. One implication of this is that it might be an orphan flare. We show that Fermi-accelerated protons of energy ≤168 TeV can interact with the low energy tail of the background synchrotron self-Compton photons in the inner region of the blazar to produce the multi-TeV flare and our r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…Our aim here is to use the photohadronic model of Sahu et al [15,[33][34][35][36] and the EBL model of Dominguez et al [19] to interpret the observed very strong VHE flare data of May 1 and the long outburst observed by HEGRA telescopes in 1997. We found that both these flares can be well explained with this model.…”
Section: Markarian 501mentioning
confidence: 99%
“…Our aim here is to use the photohadronic model of Sahu et al [15,[33][34][35][36] and the EBL model of Dominguez et al [19] to interpret the observed very strong VHE flare data of May 1 and the long outburst observed by HEGRA telescopes in 1997. We found that both these flares can be well explained with this model.…”
Section: Markarian 501mentioning
confidence: 99%
“…So the unknown internal photon density is expressed in terms of the known photon density calculated from the observed/fitted SED in the SSC region, which is again related to the observed flux in the same region. This model explains very nicely the observed TeV flux from the orphan flares of 1ES 1959+650, Mrk 421 as well as the multi-TeV flaring from M87 and Mrk 501 [29][30][31]39]. In the observer frame, the π 0 -decay photon energy E γ and the background SSC photon energy γ are related through…”
Section: Photohadronic Modelmentioning
confidence: 52%
“…We employ the photohadronic model to explain the multiTeV flaring from many HBLs [21,[29][30][31]38]. Here the standard interpretation of the leptonic model is used to explain the low energy peaks.…”
Section: Photohadronic Modelmentioning
confidence: 99%
See 2 more Smart Citations